2012
DOI: 10.1016/j.spinee.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Injection of AAV2-BMP2 and AAV2-TIMP1 into the nucleus pulposus slows the course of intervertebral disc degeneration in an in vivo rabbit model

Abstract: BACKGROUND CONTEXT Intervertebral disc degeneration (IDD) is a common cause of back pain. Patients who fail conservative management may face the morbidity of surgery. Alternative treatment modalities could have a significant impact on disease progression and patients’ quality of life. PURPOSE To determine if the injection of a virus vector carrying a therapeutic gene directly into the nucleus pulposus improves the course of IDD. STUDY DESIGN Prospective randomized controlled animal study. METHODS Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 53 publications
2
86
0
Order By: Relevance
“…In a rabbit annular stab-injury model, there was a relative decrease in BMP-2 mRNA levels, followed by a consequent increase close to the preoperative levels (20). In a prospective, randomized controlled animal study, injection of the BMP-2 gene delayed degenerative changes in a rabbit disc puncture model (23). Our results demonstrated that the number of BMP-2-positive cells in the AF increased following treatment with HGF, whereas a strong positive staining of BMP-2 was only observed in cells at the disrupted border in the AF of stab-injury only and gel alone-treated segments, suggesting that HGF promotes BMP-2-induced repair in degenerative discs.…”
Section: Discussionmentioning
confidence: 94%
“…In a rabbit annular stab-injury model, there was a relative decrease in BMP-2 mRNA levels, followed by a consequent increase close to the preoperative levels (20). In a prospective, randomized controlled animal study, injection of the BMP-2 gene delayed degenerative changes in a rabbit disc puncture model (23). Our results demonstrated that the number of BMP-2-positive cells in the AF increased following treatment with HGF, whereas a strong positive staining of BMP-2 was only observed in cells at the disrupted border in the AF of stab-injury only and gel alone-treated segments, suggesting that HGF promotes BMP-2-induced repair in degenerative discs.…”
Section: Discussionmentioning
confidence: 94%
“…BMP-2 and BMP-7 (osteogenic protein 1) act to increase proteoglycan production, specifically aggrecan and collagen types I and II in AF and NP cells [11,37,47]. Local injection of degenerative discs with BMP-2 and BMP-7 has been reported to maintain disc height and increase production of proteoglycans in both rat and rabbit models [3,31,34,41,58]. Despite successful demonstration of increased proteoglycan and collagen content, BMPs also cause ossification of the annulus and aberrant bone formation [29,35].…”
Section: Protein-based Therapiesmentioning
confidence: 99%
“…In vivo transfection of intervertebral disc cells with an adenoviral vector containing the TGF-b1 gene resulted in increased TGF-b1 expression and proteoglycan synthesis [65]. Also, successful delivery of an adeno-associated virus encoded with genes for the proanabolic molecule BMP-2 and anticatabolic molecule tissue inhibitor of matrix metalloproteinases 1 showed decreased MRI, histologic, serum biochemical, and biomechanical evidence of disc degeneration over a 12-week period [41].…”
Section: Gene-based Therapiesmentioning
confidence: 99%
“…Gene delivery of TIMP-1 has been shown to enhance proteoglycan synthesis in human degenerate IVD cells [117]. In a in vivo rabbit model of IDD, injection of adenoassociated virus serotype 2 (AAV2) vector carrying TIMP-1 gene into NP tissue remarkably enhances Col II content in the discs, followed up less MRI and histologic evidence of degeneration [118]. These data further confirm that an increased ECM production contributes to the delay of IDD progression.…”
Section: Therapeutic Potential Of Targeting Mmps and Adamtss In Iddmentioning
confidence: 61%